In the Plots of Neoliberalism: the Impact of AirBnb on Hotel Industry and the Real Estate Market in São Paulo and Rio de Janeiro, Brazil - Rita de Cássia Ariza da Cruz; Cristina Pereira de Araujo; Luciano Muniz Abreu (Via@)
With a market value of nearly US$136 billion (Nasdaq, 20242), AirBnb stands as the foremost hospitality platform in the world, with operations spanning across most countries. Introduced in Brazil in 2012, Airbnb is now present in every state of the country, dominant in cities with massive tourist influx, though it faces stiff competition from other smaller platforms. Despite the discernibly increasing impact of AirBnb in different places, only a few studies about Brazil have been carried out. In recognition of this gap, the main objective of this text is to analyze its impacts in the two largest Brazilian metropolises, São Paulo and Rio de Janeiro, considering its effects on hotel occupancy rates, ADR and RevPAR as well as on real estate market trends. As a theoretical premise, this text considers the relationship between AirBnb, the hotel industry and the real estate market as an expression of neoliberalism in the production of urban spaces in a developing country, based on the construction of a ‘market society’, on the competition between individuals and on their self-entrepreneurship (Andrade; Côrtes; Almeida, 2021). The methodological approach employed for this study comprises literature and documentary research, exploratory (considering the real estate) and comparative data analysis (on AirBnb listings and on hotel occupancy rates, ADR and RevPAR), as well as a cartographic production. The data about AirBnb was obtained from the AirDna Platform including the whole years of 2021, 2022, 2023 and January 2024, and concerning the real estate market in both cities, the main data source was SECOVI, a private entity that represents the economic category of real estate purchase, sale, rental and management companies. The results show that, given the significant geographical differences between the cities analyzed, AirBnb has produced a specific topology in each of them. Furthermore, although no evidence was found that this platform has had a significant impact on hotel occupancy rates, ADR and RevPAR in these cities in recent years, the competition between AirBnb and hotel industry is considered unfair. Finally, there are signs of an impact on the real estate market typologies in both São Paulo and Rio de Janeiro, where there has been an increase in real estate launches explicitly aimed at seasonal rentals.